Kelayakan Novel Bau Peapi (Dari Lidah Turun Ke Hati) Karya Reni Hujan Sebagai Rekomendasi Bahan Ajar Sastra di SMA - Assidiq, Aif Nurhidayat; Adham, M. Januar Ibnu; Mujtaba, Sahlan (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This study aims to assess the suitability of the novel "Bau Peapi (Dari Lidah Turun Ke Hati)" by Reni Hujan as a teaching material for literary appreciation in high schools. The research employed a qualitative method with a descriptive-analytical approach. The data were collected through content analysis of the novel and interviews with high school students. The findings indicate that the novel "Bau Peapi (Dari Lidah Turun Ke Hati)" possesses several aspects that make it suitable as a teaching resource for literary appreciation in high schools. These aspects include linguistic elements, psychological dimensions, socio-cultural backgrounds, alignment with the core competencies of Indonesian language education in high schools, and the inclusion of character education values. In conclusion, the novel "Bau Peapi (Dari Lidah Turun Ke Hati)" by Reni Hujan is deemed appropriate for use as a literary teaching material in high schools, supported by various factors such as linguistic aspects, psychological relevance, cultural background, alignment with Indonesian language competencies, and the integration of character education values. Keywords: Literary Appreciation, Teaching Material, Suitability, Novel